Method for mixing coal and binder for molding coal and method for manufacturing molding coal

By measuring its conductivity in water, the mixing conditions between coal powder and binder are adjusted by using salt as a binder substitute, the problem of crushing coal powder briquettes in the coke oven in the prior art is solved, and the effect of uniform mixing and strength improvement is achieved.

JP7665130B2Active Publication Date: 2025-04-21JFE STEEL CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022132977
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-08-24
Publication Date
2025-04-21
Estimated Expiration
2042-08-24

AI Technical Summary

Technical Problem

In the prior art, the briquet made of mixed coal powder and binder (such as starch) is easily crushed when pumped into a coke oven, and the existing mixing equipment has high cost or poor mixing performance, making it difficult to ensure uniform mixing of coal powder and binder.

Method used

Using salt as a replacement for the binder, the salt concentration of the mixture is determined by measuring the conductivity of the salt in water, thereby adjusting the mixing conditions to ensure uniform mixing of coal powder and the binder.

Benefits of technology

The uniform mixing of coal powder and adhesive is achieved, the strength of the briquet is improved, the equipment cost and measurement complexity are reduced, and the measurement results are fast and reliable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665130000002
    Figure 0007665130000002
  • Figure 0007665130000003
    Figure 0007665130000003
  • Figure 0007665130000004
    Figure 0007665130000004
Patent Text Reader

Abstract

To provide a mixing method using a technology developed to improve bonding strength of molded coal, and a production method of the molded coal using the mixing method, wherein the technology makes it possible to appropriately and easily obtain a uniform mixing state of coal that is a raw material for the molded coal, and starch that is a binder.SOLUTION: A mixing method of coal used as a raw material for molded coal and a binder comprises: determining a relationship between a concentration of salt in water and conductivity in advance using the salt as a binder substitute; putting the coal and the salt into a mixer to mix; collecting a raw material mixture at each predetermined position in the mixer; stirring the raw material mixture with the water to measure the conductivity of the water with dissolved salt; calculating the concentration of the salt in the raw material mixture from the relationship between the concentration of the salt in the water and the conductivity; and mixing the coal and the binder according to a mixing condition of the coal and the binder if the concentration falls within a desired concentration range.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for mixing coal and a binder in a molded coal raw material and a method for producing molded coal. In particular, the present invention relates to a mixing method that can easily determine the mixing ratio of coal and a binder in a molded coal raw material in order to improve the strength of the molded coal so that it is not crushed when charged into a coke oven. [Background technology]

[0002] Conventionally, in a coke oven, coal is put in and carbonized to produce coke, but there has been a demand for utilizing coal powder (hereinafter also referred to as "powdered coal") that is generated when handling coal. One of the methods for utilizing coal is to mix a binder called a binder with the coal powder to produce molded coal. Conventionally, relatively inexpensive tar pitch and asphalt pitch have been used as typical binders for molded coal, but the odor caused by volatile components generated from the pitch can be a problem, and starch has been attracting attention in recent years as a binder that does not generate odor. For example, as described in Patent Document 1, molded coal is produced by mixing starch (starch) as a binder with coal powder, and the molded coal is put into a coke oven.

[0003] However, molded coal, which is simply made by mixing coal powder with starch as a binder, has a problem in that it has lower strength than coal and is easily crushed when placed in a coke oven.

[0004] Meanwhile, for mixing coal and starch, for example, a batch-type vertical mixer such as a Henschel mixer as described in Patent Document 2, or a horizontal mixer called a kneader capable of stirring and mixing using a stirring blade as described in Patent Document 3 is used.

[0005] A vertical Henschel mixer, which is an example of a vertical mixer shown in Figure 4, has a high rotation speed of the rotating blades and high mixing performance (close to complete mixing), but the equipment costs are high. Also, a horizontal kneader mixer, which is an example of a horizontal mixer shown in Figure 7, has low equipment costs but is said to have inferior mixing performance.

[0006] To improve the strength of molded coal using these mixers, the amount of coal and starch mixed must be appropriate and mixed uniformly. To do this, it is necessary to understand the mixing state of coal and starch and determine the optimal mixing conditions.

[0007] Conventionally known methods for determining the mixed state of coal and binder include the sulfur concentration measurement method described in Patent Document 4 and the absorbance measurement method described in Patent Document 1.

[0008] However, the chemical analysis methods such as the sulfur concentration measurement described in Patent Document 4 and the photometric methods such as the absorbance measurement method described in Patent Document 1 require expensive measuring devices, complicated measurement procedures that require specialized skills, and require a long time to obtain results, so they are not rapid and efficient. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Patent Publication No. 2021-177165 [Patent Document 2] Japanese Utility Model Application Publication No. 61-152405 [Patent Document 3] JP 2009-028650 A [Patent Document 4] International Publication No. WO2015-177998 Summary of the Invention [Problem to be solved by the invention]

[0010] Therefore, the present invention aims to develop a technique for appropriately and simply determining the mixed state of the coal as the raw material for molded coal and the starch as the binder in order to improve the binding strength of molded coal, and to provide a mixing method using the technique, and further to provide a manufacturing method for molded coal using the mixing method. [Means for solving the problem]

[0011] Conventionally, in order to grasp the mixed state of coal and binder, the mixture itself has been measured, which has the problem that the measuring equipment is expensive and the procedure is complicated.

[0012] The present inventors have conducted extensive research to solve the above problems, and as a result, have found that since the amount of binder to be mixed is small, about 1 wt% (weight %) compared to the amount of coal, it is effective to use "salt," an inexpensive material, as an indicator to substitute for the binder in order to grasp the mixed state of the binder.

[0013] The present invention was completed based on these findings and through further investigation, and the gist of the present invention is as follows. [1] A method for mixing coal, which is the raw material for molded coal, with a starch-based binder, comprising the steps of: a preliminary measurement step (1) of determining a relationship between a concentration of the salt in water and electrical conductivity using salt as a substitute for the binder; a sample mixing step (2) of feeding the coal and the salt into a mixer under predetermined mixing conditions and mixing them; A specific position sampling step (3) of sampling the raw material mixture at a specific position in the mixer after mixing; a conductivity measuring step (4) of stirring the sampled raw material mixture with a certain amount of water to dissolve the salt in the raw material mixture in the water and measuring the conductivity of the water in which the salt is dissolved; a specific position salt concentration calculation step (5) for calculating the concentration of salt in the raw material mixture at the specific position from the relationship obtained in the advance measurement step (1); a specific position salt concentration comparison step (6) of comparing the salt concentration obtained in the specific position salt concentration calculation step (5) with a desired concentration range of the binder, and if the salt concentration is not within the desired concentration range of the binder, changing the predetermined mixing conditions and repeating the steps from the sample mixing step (2); a mixing condition determination step (7) of determining the predetermined mixing conditions as mixing conditions for the binder when the concentration of the salt falls within a desired concentration range for the binder; a coal-binder mixing step (8) of mixing the coal and the binder in an actual operation according to the determined mixing conditions; A method for mixing coal and a binder for forming molded coal, comprising the steps of: [2] A method for mixing coal, which is a raw material for molded coal, with a starch-based binder, comprising the steps of: a preliminary measurement step (1) of determining a relationship between a concentration of the salt in water and electrical conductivity using salt as a substitute for the binder; a sample mixing step (2) of feeding the coal and the salt into a mixer under predetermined mixing conditions and mixing them; a multi-position sampling step (13) of sampling the raw material mixture at each of multiple positions in the mixer after mixing; a conductivity measuring step (4) of stirring the sampled raw material mixture with a certain amount of water to dissolve the salt in the raw material mixture in the water and measuring the conductivity of the water in which the salt is dissolved; a multi-position salt concentration calculation step (15) for calculating the salt concentration in the raw material mixture at each of the multiple positions from the relationship obtained in the advance measurement step (1); a salt concentration distribution determination step (16) of changing the predetermined mixing conditions and repeating the process from the sample mixing step (2) if the salt concentration distribution obtained in the multiple-position salt concentration calculation step (15) does not fall within a desired concentration distribution range; a mixing condition determination step (7) of determining the predetermined mixing conditions as mixing conditions for the binder when the concentration distribution of the salt falls within a desired concentration distribution range; a coal-binder mixing step (8) of mixing the coal and the binder in an actual operation according to the determined mixing conditions; A method for mixing coal and a binder for forming molded coal, comprising the steps of: [3] A method for mixing coal and a binder for a molded coal raw material, characterized in that in the salt concentration distribution determination step (16) described in [2] above, a standard deviation σ of the mixing ratio of the coal and the salt is calculated, and if the standard deviation is outside a desired value, the specified mixing conditions are changed and the process is repeated from the sample mixing step (2). [4] The method for mixing coal and a binder for forming molded coal according to any one of [1] to [3] above, wherein the predetermined mixing condition is a mixing time. [5] The method for mixing coal and a binder for forming molded coal raw material according to any one of [1] to [3], wherein the predetermined mixing condition is a position at which the binder is introduced into the mixer. [6] A method for producing molded coal, comprising mixing the coal and the binder by using the mixing method according to any one of [1] to [3] above, and molding the resulting mixture. Effect of the Invention

[0014] In the present invention, in order to grasp the mixed state of coal and binder in the molded coal raw material, salt is used as a substitute for the binder, and the mixture is dissolved in water and the conductivity is measured, thereby making it possible to grasp the mixed state (variation in concentration) easily and accurately at low cost and without requiring specialized skills. In addition, the measurement of conductivity can be performed quickly, so the measurement time can be shortened. [Brief description of the drawings]

[0015] [Figure 1] 1 is a flow chart showing the steps of a mixing method using location-specific sampling according to the present invention. [Diagram 2] FIG. 2 is a diagram showing an example of the relationship between the concentration of a salt used in the mixing method according to the present invention and electrical conductivity. [Diagram 3] 1 is a flow chart showing steps of a multi-site sampling mixing method according to the present invention. [Figure 4] FIG. 1 is a schematic cross-sectional view showing an overview of a Henschel mixer, which is an example of a vertical mixer. [Diagram 5] FIG. 1 is a schematic diagram for explaining an outline of a sample collection position and a method for measuring electrical conductivity when a vertical mixer is used. [Figure 6] FIG. 1 is a schematic diagram showing the measurement results of salt concentration in a mixture sample when a vertical mixer is used. [Figure 7] FIG. 1 is a schematic cross-sectional view showing an overview of a horizontal kneader mixer, which is an example of a horizontal mixer. [Figure 8] FIG. 1 is a schematic diagram illustrating sample collection positions when a horizontal mixer is used. [Figure 9] FIG. 2 is a schematic diagram showing the position where salt is introduced into a horizontal mixer and the measurement results of the salt concentration after mixing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, a representative embodiment of a method for mixing coal and a binder as a raw material for molded coal according to the present invention and a method for producing molded coal using the mixing method will be described in detail with reference to the drawings. In addition, since the drawings are intended to conceptually explain the present invention, the dimensions and ratios of each member shown in the drawings may differ from the actual ones.

[0017] [Manufacturing method of molded charcoal] First, an example of a method for producing molded coal used in a coke production process will be described. Starch is mixed with a portion of the coal powder (fine coal), which is the raw material for molded charcoal, and the mixture is put into a molding machine to obtain molded charcoal.

[0018] The type of starch used may be, for example, starch produced from raw plant materials such as tapioca, potato, sweet potato, corn, rice, wheat, etc. Starch derivatives obtained by processing starch derived from plants and chemically synthesized starches may also be used.

[0019] [Mixing method step 1] Next, a method for mixing coal and a binder for forming briquettes according to the present invention will be described. Each step of procedure 1 regarding the mixing method will be described with reference to the flow chart in FIG.

[0020] In the "pre-measurement step" (1), the relationship between the salt concentration in water and the electrical conductivity is determined in advance using salt as a substitute for the binder. As an example of this relationship, a calibration curve of the salt concentration in water (g-salt / L-water) and electrical conductivity (mS / cm) is shown in Figure 2.

[0021] In the “sample mixing process” (2), coal and salt are put into the target mixer under specified mixing conditions and mixed.

[0022] In the "specific position sample collection step" (3), after mixing in the above-mentioned "sample mixing step" (2), the mixture (sample) is collected at a specific position in the mixer.

[0023] In the "conductivity measurement process" (4), the raw material mixture collected in the "specific position sample collection process" (3) is stirred with a certain amount of water to dissolve the salt in the raw material mixture in the water, and the conductivity of the water with the salt dissolved in it is measured.

[0024] In the "specific position salt concentration calculation process" (5), the salt concentration in the raw material mixture is calculated from the conductivity measured in the "conductivity measurement process" (4) above, using the relationship between the salt concentration in water and the conductivity determined in the "pre-measurement process" (1) above.

[0025] On the other hand, the theoretical concentration of the binder (hereinafter also referred to as the "completely mixed concentration") (wt%) assuming completely uniform mixing (hereinafter also referred to as "complete mixing") can be calculated from the ratio of the total weight of the binder to the sum of the total weight of the coal to be mixed and the total weight of the binder to be mixed.

[0026] Therefore, in the "specific position salt concentration comparison step" (6), the conductivity of the mixture of coal and salt collected from the specific position is measured to determine the salt concentration (mixed state), and the measured value is compared with the above-mentioned completely mixed binder concentration. If the difference is not within the desired range, the process returns to the "sample mixing step" (2), and the mixture is mixed under different predetermined mixing conditions, and the "specific position sample collection step" (3), the "conductivity measurement step" (4), the "specific position salt concentration calculation step" (5), and the "specific position salt concentration comparison step" (6) are repeated.

[0027] In the "specific position salt concentration comparison process" (6), the above measured value is compared with the completely mixed concentration of the binder, and if the difference is within a desired range, it can be determined as the mixing condition of the binder in the "mixing condition determination process" (7).

[0028] In the “coal-binder mixing process” (8), the coal and binder are mixed according to the determined mixing conditions.

[0029] [Mixing method step 2] Next, each step of procedure 2 relating to the method for mixing coal and a binder for forming molded coal according to the present invention will be described with reference to the flowchart of FIG.

[0030] In the “pre-measurement step” (1), similar to step 1 of the mixing method described above, a calibration curve is obtained in advance, using salt as a substitute for the binder, showing the relationship between the salt concentration in water and the electrical conductivity, an example of which is shown in FIG. 2.

[0031] In the “sample mixing process” (2), similar to step 1 of the mixing method described above, coal and salt are put into the target mixer and mixed under specified mixing conditions.

[0032] In the "multiple position sampling step" (13), after mixing in the above-mentioned "sample mixing step" (2), the mixed raw material mixture (samples) is sampled at each of a plurality of predetermined positions in the mixer.

[0033] In the "conductivity measurement process" (4), the raw material mixture collected at each of the multiple positions in the "multiple position sample collection process" (13) is stirred with a fixed amount of water to dissolve the salt in the raw material mixture in the water, and the conductivity of the water with the salt dissolved in it is measured.

[0034] In the "multiple-location salt concentration calculation process" (15), the salt concentration in the raw material mixture at each of the multiple locations is calculated using the calibration curve obtained in the "pre-measurement process" (1) from the conductivity measured in the "conductivity measurement process" (4).

[0035] In the "salt concentration distribution determination process" (16), it is determined whether the distribution of the measured values ​​obtained in the "multiple-position salt concentration calculation process" (15) falls within the desired concentration distribution range. For example, it is determined whether the difference in concentration at each position falls within the desired range in the concentration distribution at multiple positions. If the difference does not fall within the desired range, the process returns to the "sample mixing process" (2), changes the specified mixing conditions, and mixes the samples, and then repeats the "multiple-position sample collection process" (13), the "conductivity measurement process" (4), the "multiple-position salt concentration calculation process" (15), and the "salt concentration distribution determination process" (16).

[0036] In the "mixing condition determination step" (7), if the difference in concentration at each position in the "salt concentration distribution evaluation step" (16) falls within a desired range, the mixing conditions for the binder can be determined.

[0037] In the “coal-binder mixing process” (8), the coal and binder are mixed according to the determined mixing conditions.

[0038] Furthermore, in the above-mentioned "multiple-position salt concentration calculation step" (15), it is advisable to calculate not only the salt concentration but also the standard deviation σ of the mixture ratio.

[0039] In the "salt concentration distribution determination process" (16), it is determined whether the standard deviation σ of the mixing ratio is within a desired range. For example, in the concentration distribution at multiple positions, it is determined whether the standard deviation σ of the mixing ratio at each position is within a desired range. If the standard deviation is not within the desired range, the process returns to the "sample mixing process" (2), changes the mixing conditions, and mixes the samples, and then repeats the "multiple-position sample collection process" (13), the "conductivity measurement process" (4), the "multiple-position salt concentration calculation process" (15), and the "salt concentration distribution determination process" (16).

[0040] [Production of molded charcoal] By mixing coal and binder under the actual operational mixing conditions determined in the above “Coal-Binder Mixing Process” (8) for each mixer used, molded coal with improved strength can be produced.

[0041] [Salt as a binder substitute] Next, the reason why salt is used as a binder substitute in order to select the mixing conditions in the present invention will be explained.

[0042] Salt, whose main component is sodium chloride (NaCl), can be mixed with coal as fine solids. In addition, if a sample taken after mixing is mixed with a certain amount of water, only the salt will dissolve easily in the water, so the salt content can be easily obtained by measuring the electrical conductivity of the salt solution. Furthermore, since the relationship between the concentration of the salt solution and electrical conductivity is almost linear, the salt content in a certain amount of water can be calculated from the electrical conductivity, and the mixed state can be calculated from the salt content and the weight of the sampled mixture. The measurement of electrical conductivity is specified in JIS K 0130 "General rules for measuring electrical conductivity."

[0043] [How to obtain the calibration curve] Figure 2 shows an example of the relationship between salt concentration and conductivity, which was determined in advance in the pre-measurement step (1) of the mixing method described above. The results show the results of dissolving 0 g, 0.5 g, 1.0 g, and 2.0 g of salt in 1 L of water and measuring the conductivity of each. As shown in Figure 2, a calibration curve was obtained for the relationship expressed by the following formula (1). y=1.6098x+0.2844 (1) Here, x is the salt concentration (g-salt / L-water) and y is the electrical conductivity (mS / cm).

[0044] In addition, the coefficient of determination of the calibration curve (regression equation) is R 2 =0.9999, showing an extremely high correlation.

[0045] Therefore, from the above equation (1), the salt concentration (x) can be calculated by measuring the conductivity (y) of water with dissolved salt.

[0046] [Standard deviation of mixture ratio σ] Concentration C of the component of interest in the samples taken from each measurement position in the mixer i The standard deviation σ for the average concentration C0 is expressed by the following formula (I).

[0047]

number

[0048] In the present invention, the concentration C i is the salt concentration [wt%] of each sample. The average concentration C0 is the concentration in a completely mixed state, and corresponds to the salt concentration [wt%] added to the entire sample. The above standard deviation σ can be calculated using samples taken from multiple sampling positions. EXAMPLES

[0049] The embodiments of the present invention will be described in more detail below with reference to examples. In order to demonstrate that coal and binder can be mixed uniformly by the mixing method according to the present invention, a study was conducted to determine the mixing conditions for coal and binder using two types of mixing equipment (a vertical mixer, a Henschel mixer, and a horizontal mixer, a horizontal kneader mixer) described below.

[0050] The method of investigation involved putting coal and salt into a mixer. The coal and salt were mixed for a set mixing time, and after mixing, samples were taken from set positions (10 positions) in the mixer. A set amount of water was mixed into the collected samples (raw material) and the conductivity was measured. The salt content was determined by comparing with the conductivity of water alone. The results are explained below.

[0051] [When using a vertical mixer] First, 1 wt% salt was added to the coal using a Henschel mixer as shown in Figure 4, and the mixing time was varied from 5 seconds to 600 seconds. The concentration of the completely mixed salt was 1 wt%.

[0052] For the mixtures mixed for 5, 180 and 600 seconds, 50g of mixture samples were taken from 10 sampling positions in the Henschel mixer as shown in Fig. 5(a) in top view. The sampled mixtures were then poured into a 500cm 3The salt was dissolved in 100 g of water and the conductivity (mS / cm) was measured. The salt concentration (wt%) was calculated from the conductivity using the calibration curve in Figure 2, and the weight of the salt relative to the amount of water used for dissolution was calculated from the salt concentration. The salt concentration (wt%) of the mixture at each sampling point was calculated using the weight of the salt as the standard weight of the sampled mixture (50 g). The results are shown in Figure 6.

[0053] It was found that in the case of a mixing time of 5 seconds in Figure 6(a), the salt concentration varied greatly at each sampling position in the Henschel-type mixer compared to the case of a complete mixing of 1 wt%, and it was found that a mixing time of 5 seconds was not appropriate.

[0054] In addition, when the mixing time in Figure 6(b) reached 180 seconds, the salt concentration at each sampling point approached that in the case of complete mixing of 1 wt%, indicating a relatively good mixing state.

[0055] Furthermore, it was found that when the mixing time in Figure 6(c) was sufficiently secured at 600 seconds, the salt concentration at each sampling point was mixed until it approached 1 wt% (complete mixing).

[0056] From the above results, it was found that when using a Henschel-type vertical mixer, in order to improve the strength of molded coal using a mixture of coal and binder, the mixing time of coal and binder needs to be kept up to 600 seconds.

[0057] [When using a horizontal mixer] Next, the following study was carried out using the horizontal kneader mixer shown in FIG. The top cover of this horizontal kneader mixer can be opened and closed along its entire length, so the position at which salt, a substitute for starch, was added was changed and mixed. The ratio of salt to the total coal was set to 1 wt%. As shown in Figure 8, the addition position of the salt in the horizontal kneader mixer was divided into 10 parts in the longitudinal direction of the mixer, and 100 g of mixture samples were collected at each division. The mixture samples were then spread over a 1000 cm 3 The relationship between the salt concentration (wt%) and the conductivity was determined using the calibration curve shown in Figure 2.

[0058] The salt concentration was calculated from the measured conductivity, and the weight of the salt was calculated from the salt concentration and the amount of water used to dissolve it. The salt concentration distribution of the mixture was calculated from the weight of the salt using the weight of the sampled mixture (100 g) as the base. The results are shown in Figure 9.

[0059] In the case of the horizontal kneader mixer, the amount of salt added was intentionally made uneven, specifically, the salt was added unevenly from the upper part of the mixer.

[0060] As shown in Figure 9(a), when mixing was performed without adding salt to the horizontal kneader mixer at approximately the left 1 / 4 position of the mixer, the salt concentration in the left 1 / 4 position of the mixer was significantly reduced, as shown in the graph in Figure 9(a).

[0061] In contrast, as shown in Figure 9(b), when the salt was added to the horizontal kneader mixer almost evenly, it was found that a state close to complete mixing was achieved.

[0062] From the above results, it was found that the salt injection position has a large effect in the case of a horizontal kneader mixer. Therefore, when using a horizontal kneader mixer, it is important to inject almost equal amounts of coal and binder along the entire length of the mixer in order to obtain a molded product with sufficient strength using the mixture obtained from the horizontal kneader mixer.

[0063] [Determining mixing conditions] As explained above, in order to determine the optimal mixing conditions for coal and binder, it is necessary to grasp in advance the change in the mixing ratio of coal and binder for each mixer to be used and to determine efficient mixing conditions for each mixer. As a method for this purpose, it was found that the method of the present invention, in which salt is used as a substitute for binder to examine the mixing state with coal, is a method that can easily and appropriately determine the mixing state and can obtain excellent effects that have not been achieved in the past. [Explanation of symbols]

[0064] 1 Vertical mixer body 2 Rotation Axis 3, 4 Rotating blades 11 Horizontal mixer body 12 Rotation axis 13 Screw blade

Claims

1. A method for mixing coal as a raw material for molded coal with a starch-based binder, comprising the steps of: a preliminary measurement step (1) of determining a relationship between a concentration of the salt in water and electrical conductivity using salt as a substitute for the binder; a sample mixing step (2) of feeding the coal and the salt into a mixer under predetermined mixing conditions and mixing them; A specific position sampling step (3) of sampling the raw material mixture at a specific position in the mixer after mixing; a conductivity measuring step (4) of stirring the collected raw material mixture with a certain amount of water to dissolve the salt in the raw material mixture in the water and measuring the conductivity of the water in which the salt is dissolved; a specific position salt concentration calculation step (5) of calculating the concentration of salt in the raw material mixture at the specific position from the relationship obtained in the preliminary measurement step (1); a specific position salt concentration comparison step (6) of comparing the salt concentration obtained in the specific position salt concentration calculation step (5) with a desired concentration range of the binder, and if the salt concentration is not within the desired concentration range of the binder, changing the predetermined mixing conditions and repeating the sample mixing step (2) and the like; a mixing condition determination step (7) of determining the predetermined mixing conditions as mixing conditions for the binder when the concentration of the salt falls within a desired concentration range for the binder; A coal / binder mixing step (8) of mixing the coal and the binder in actual operation according to the determined mixing conditions; A method for mixing coal and a binder for forming molded coal, comprising the steps of:

2. A method for mixing coal as a raw material for molded coal with a starch-based binder, comprising the steps of: a preliminary measurement step (1) of determining a relationship between a concentration of the salt in water and electrical conductivity using salt as a substitute for the binder; a sample mixing step (2) of feeding the coal and the salt into a mixer under predetermined mixing conditions and mixing them; A multi-position sampling step (13) of sampling the raw material mixture at each of multiple positions in the mixer after mixing; a conductivity measuring step (4) of stirring the collected raw material mixture with a certain amount of water to dissolve the salt in the raw material mixture in the water and measuring the conductivity of the water in which the salt is dissolved; a multi-position salt concentration calculation step (15) for calculating the salt concentration in the raw material mixture at each of the multiple positions from the relationship obtained in the advance measurement step (1); a salt concentration distribution determination step (16) of changing the predetermined mixing conditions and repeating the sample mixing step (2) and the like when the salt concentration distribution obtained in the multiple-position salt concentration calculation step (15) does not fall within a desired concentration distribution range; a mixing condition determination step (7) of determining the predetermined mixing conditions as mixing conditions for the binder when the concentration distribution of the salt falls within a desired concentration distribution range; A coal / binder mixing step (8) of mixing the coal and the binder in actual operation according to the determined mixing conditions; A method for mixing coal and a binder for forming molded coal, comprising the steps of:

3. The method for mixing coal and a binder for a molded coal raw material according to claim 2, characterized in that in the salt concentration distribution determination step (16), a standard deviation σ of the mixing ratio of the coal and the salt is calculated, and if the standard deviation is outside a desired value, the predetermined mixing conditions are changed and the process is repeated from the sample mixing step (2).

4. 4. The method for mixing coal and a binder for forming briquetted coal according to claim 1, wherein the predetermined mixing condition is a mixing time.

5. 4. The method for mixing coal and a binder for forming molded coal raw material according to claim 1, wherein the predetermined mixing condition is a position at which the binder is introduced into the mixer.

6. A method for producing molded coal, comprising the steps of: mixing the coal and the binder by using the mixing method according to any one of claims 1 to 3; and molding the mixture.

Citation Information

Patent Citations

  • JP1986152405U

  • Formed coal and method for producing the same

    JP2003064377A

  • Stirring device and dryer

    JP2009028650A

  • Coke production method

    JP2014105213A

  • Binder quantifying method for briquette raw material powder and / or briquette, binder dispersion evaluating method for briquette raw material powder and / or briquette, manufacturing method for briquette, and briquette

    JP2021177165A